Fat Girl, Terrestrial : A Novel - Wells, Kellie, 1962- (Book collections on Project MUSE., 2012)
Not only the story of a colossus of a woman living in Kansas, Fat Girl, Terrestrial is also a meditation on God, treachery, and blind love. In Kingdom Come, Kansas, a town from which children once mysteriously disappeared, there lives a giant woman. Wallis Armstrong is not a pituitary mutant or a person battling a rare medical condition; she's just an improbably large woman ill at ease in a world built for shrimps. Paradoxically, Wallis builds miniatures of crime scenes, and her specialty is staged suicides. She constructed her first diorama as a child.